SEROPREVALENCE OF IgG ANTI-T. GONDII ANTIBODY AMONG HIV-INFECTED PATIENTS IN MAIDUGURI, NORTH EASTERN NIGERIA - Goni BW; Bakki B; Kida IM; Yusuph H; Zailani SB; Mustapha SK; Tahir A; Sahabi MA; Talle MA; Baba MM; Balarabe SA; Garbati MA; et al. (Ntec Specialist, 2012)
Background: Toxoplasma gondii infection is one of the commonest opportunistic infections in HIV-infected patients, with the fatal consequences of toxoplasmic encephalitis particularly in advanced disease. However, data regarding T. gondii infection in the setting of HIV/AIDS are scant in Nigeria. Objective: To determine the seroprevalence of T. gondii amongst HIV-infected patients as well as to determine the correlation between anti-T. gondii IgG titre and the CD4+ cell count/HIV-1 RNA viral load. Method: A cross sectional study in which a total of 190 subjects were involved i.e. 110 newly diagnosed HAART naïve HIV-positive patients and 80 apparently healthy HIV-negative age- and sex-matched controls that were selected by simple random sampling method. Results: The age range of the study population was 20-64 years. The mean ages of male subjects for both HIV-positives and controls were 37.52 ±8.20 years and 35.79 ±12.31years, respectively, (p= 0.462). On the other hand, the mean ages of female subjects for both HIV-positives and controls were 29.90 ±6.98 years and 32.30 ±10.29 years, respectively, (p=0.149). Twenty one subjects (19.1%) among HIV-positives and 1 (1.25%) HIV-negative tested positive for anti-T. gondii IgG, respectively, (p= 0.000). The prevalence rate ratio of anti-T. gondii IgG of HIV positives compared to HIV negatives was 15.28. Significant proportion of anti-T.gondii positive subjects presented with AIDS defining illnesses compared with their anti-T.gondii negative counterparts. Conclusion: The study has shown that anti-T. gondii IgG is about 15 times more prevalent among HIV positive patients compared to controls. Routine screening for T. gondii IgG anti-body is therefore recommended for all HIV-infected subjects at the facility as well as commencement of chemoprophylaxis against Toxoplasmic encephalitis in HIV-infected patients with CD4+ cell count of 100 cells/ml